PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS ANDROID TERHADAP HASIL BELAJAR MAHASISWA - Budiarti, Yesi; Tantri, Reni (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2019)
Audio-visual media is a media that can display elements of images and sound elements in an integrated manner when communicating messages or information. Audio visual media is an intermediary media or the use of material and its absorbers through sight and hearing. Thus building conditions that can make students able to gain knowledge, skills and attitudes. The purpose of this study was to determine